Enhancing the Impact of Indonesian Scientific Publications: Policy Strategies for Improving the FWCI - Parama Tirta Wulandari Wening Kusuma (Jurnal Indonesia Sosial Sains, 2026)
The rapid growth of scientific publications has shifted research evaluation from publication quantity toward scientific quality and citation impact. One of the most widely accepted indicators of research influence is the Field-Weighted Citation Impact (FWCI), which measures citation performance relative to the global average within the same discipline, publication type, and year. Although Indonesia has experienced remarkable growth in publication output and international visibility, its FWCI remains below the global average, indicating that increased visibility has not been translated into proportional scientific influence. This study aims to formulate evidence-based policy strategies to improve the FWCI of Indonesian scientific publications through a comparative analysis of publication performance and policy interventions. An explanatory comparative research design with an ex post facto approach was employed using secondary data obtained from SciVal, national policy documents, and relevant international literature. Data were analyzed descriptively and comparatively using the Ultrasound (Urgency–Seriousness–Growth) method, the Five Whys analysis, Dunn’s policy evaluation framework, and an Impact–Feasibility Priority Matrix. The findings reveal that Indonesia occupies a unique position in ASEAN, characterized by high publication visibility but relatively low citation impact. The analysis identifies quantity-oriented publication policies, limited international collaboration, insufficient researcher competencies, and inadequate support for high-impact publications as the principal barriers to improving FWCI. Among the evaluated policy alternatives, strengthening researcher competencies achieved the highest priority because of its high feasibility, broad institutional reach, and long-term effectiveness. The study concludes that integrating competency development, impact-based incentives, strategic international collaboration, and support for publication in reputable journals is essential to enhance Indonesia’s global research competitiveness and sustainably improve its FWCI.